The history of cerebrospinal fluid analysis in Brazil - Jose Antonio Livramento; Luis dos Ramos Machado (Arquivos de Neuro-Psiquiatria)
Analysis on cerebrospinal fluid (CSF) in neurological diagnosis has always been considered to be a strong point among the main complementary examinations in Brazil. The present paper reviews the main events in the history of CSF in the neurological sciences, with emphasis on the founders of several CSF schools in our country from the beginning of the 20th century to the present time.